Energy transitions, air quality and health - Pereira, Gavin; Bell, M.L.; Honda, Y.; Lee, J.T.; Morawska, L.; Jalaludin, B. (IOP Publishing Ltd, 2021)
The way we produce and use energy is transforming. Policy in this area intersects decisions that affect climate change, air quality, and the economy. The exponential increase in use of fossil fuel and nuclear energy has now essentially replaced human and animal energy (McKinney 2019 Curr. Pollut. Rep. 5 394–406; Solomon and Krishna 2011 Energy Policy 39 7422–31). These transitions have contributed to notable gains, such as improvements in mortality rates attributable to improved heating, water quality and transportation (Rayner 2012 Ecological Public Health: Reshaping the Conditions for Good health/Geof Rayner and Tim Lang (Abingdon, Oxon: Earthscan); Rosen 2015 A History of Public Health (Jhu Press); Pain 2017 Nature 551 S134–7; Cutler and Miller 2005 Demography 42 1–22). However, such transitions have also been accompanied by health detriments. Improvements in transportation and occupational efficiencies have promoted lifestyle transitions that have contributed to the chronic disease epidemic (Heath 2009 Am. J. Lifestyle Med. 3 27S–31S). Certain energy-related accidents and waste products have been long-established as carcinogenic (Guizard et al 2001 J. Epidemiol. Community Health 55 469; Cardis and Hatch 2011 Clin. Oncol. 23 251–60) and potential precursors to genetic mutations (Beir 1990 Health Effects of Exposure to Low Levels of Ionizing Radiation (Washington, DC: National Academy of Sciences); Desouky et al 2015 J. Radiat. Res. Appl. Sci. 8 247–54). Moreover, air pollution emissions are increasingly becoming recognised as a major contributor the global burden of disease, particularly cardiovascular and respiratory mortality (Cohen et al 2017 Lancet 389 1907–18). Although renewable energies can be perceived as ‘clean’, the shift to renewables has been relatively more recent and consequently, less is known about associated health impacts. The life course of renewable energy begins with the process of manufacturing renewable technologies, includes the means of transportation for the distribution and collection of these technologies as well as the disposal of their waste products and subsequent contamination. All of these stages have potential to involve direct chemical exposures through the groundwater, soil or air; and have potential to affect health through indirect pathways. A relatively understudied area, and the topic of this Focus Issue on Energy Transitions, Air Quality and Health, is the relevance of energy transitions and their associated environmental factors in a contemporary setting, how such factors affect health now, and will affect health in future.